Remote Exercise Training Intervention During the COVID-19 Pandemic: Randomized Controlled Trial - Keito F A Philippi; Peter Zeier; Alexandra Brahmer; Elmo W I Neuberger; Magdalena Sandner; Matthias Hagenah; Thilo Porten; Regina Lenz; David T Ochmann; Florian Wedekink; Jörg Wischhusen; Beat Lutz; et al. (JMIR Publications, 2024)
BackgroundSocietal measures to contain the spread of COVID-19 (eg, lockdown and contact restrictions) have been associated with decreased health and well-being. A multitude of prepandemic studies identified the beneficial effects of physical exercise on both physical and mental health. ObjectiveWe report on the feasibility of a remote physical exercise intervention and its stress-buffering potential in 2 untrained cohorts: a pre-COVID-19 cohort that completed the intervention in 2019 and a lockdown cohort that started the intervention shortly before pandemic-related restrictions were implemented. MethodsIn a randomized controlled trial, participants were assigned to either an intervention group (IG; pre-COVID-19 cohort: n=7 and lockdown cohort: n=9) or a control group (CG; pre-COVID-19 cohort: n=6 and lockdown cohort: n=6). IG participants received weekly individualized training recommendations delivered via web-based support. The intervention period was initially planned for 8 weeks, which was adhered to in the pre-COVID-19 cohort (mean 8.3, SD 0.5 weeks) but was extended to an average of 17.7 (SD 2.0) weeks in the lockdown cohort. Participants' health parameters were assessed before and after the intervention: aerobic capacity was measured as peak oxygen uptake (VO2peak) via cardiopulmonary exercise testing. Depressive symptoms were scored via the depression subscale of the Brief Symptom Inventory-18. ResultsDropout rates were low in both cohorts in the IG (pre-COVID-19 cohort: n=0, 0% and lockdown cohort: n=2, 16.7%) and the CG (pre-COVID-19 cohort: n=0, 0% and lockdown cohort: n=2, 20%). The mean adherence to the training sessions of the IG for both cohorts was 84% (pre-COVID-19 cohort: SD 5.5% and lockdown cohort: SD 11.6%). Aligned rank transform ANOVAs in the lockdown cohort indicated deterioration of VO2peak and depressive symptoms from before to after the intervention in the CG but no longitudinal changes in the IG. Analyses in the pre-COVID-19 cohort revealed significant increases in VO2peak for the IG compared to the CG (P=.04) but no intervention effects on depressive symptoms. ConclusionsWith low dropout rates and high adherence, the remote intervention was feasible for healthy adults under regular conditions and in the face of pandemic-related stressors. Moreover, our results hint at a stress-buffering effect as well as a buffering of a lockdown-induced deconditioning of remote physical exercise interventions in the pandemic scenario, which can be used in future studies to overcome equally stressful periods of life. However, due to limited statistical power, these findings should be replicated in similar scenarios. Trial RegistrationGerman Clinical Trials Register DRKS00018078; https://drks.de/search/en/trial/DRKS00018078